GM-CSF promoted DC recruitment and survival governs the intestinal mucosal response to enteric attaching-and-effacing bacterial pathogens - Hirata, Yoshihiro (2010)
The attaching-and-effacing (A/E) lesion-causing enteric pathogen, Citrobacter rodentium, was used to probe the importance of GM-CSF in mucosal protection against enteric bacterial infection. C. rodentium infection increased GM-CSF production and CD11c(+) dendritic cells (DC) in the colon of wild-type mice. After infection, mice lacking GM-CSF (GM-CSF(-/-)) had significantly fewer mucosal CD11c(+) DC, greater bacterial burden, increased mucosal inflammation and systemic spread of infection, decreased antibody responses to C. rodentium, and delayed pathogen clearance. The defective mucosal response to infection in GM-CSF(-/-) mice was rescued by GM-CSF and mimicked by CD11c(+) DC depletion in infected wild-type mice, indicating that CD11c(+) DC are major targets of GM-CSF in the intestinal mucosa in vivo. Diminished mucosal DC numbers in infected GM-CSF(-/-) mice reflected decreased DC survival and recruitment within the colon mucosa. The latter was related to a failure to upregulate epithelial cell production of the DC chemoattractant chemokine, CCL22, in the absence of GM-CSF.